MULTILINGUAL FINANCIAL CONSULTING: A STRATEGIC ASSET IN A CULTURALLY DIVERSE U.S. MARKET - Testoni, Felipe Oscar (LUMEN ET VIRTUS, 2023)
The United States is home to one of the most linguistically and culturally diverse populations in the world. With over 67 million residents speaking a language other than English at home, the need for multilingual financial consulting services has grown significantly. This paper explores how multilingualism enhances client trust, improves financial literacy, and strengthens market reach for boutique financial consulting firms. Drawing on recent data from the U.S. Census Bureau, academic literature, and industry case studies, the article argues that multilingual consulting is not merely an inclusive practice but a critical strategic advantage in the competitive U.S. market.